Chemical analyses of dredged spoil disposal sites at the Belgian part of the North Sea. (August 2016) - De Witte, Bavo; Ruttens, Ann; Ampe, Bart; Waegeneers, Nadia; Gauquie, Johanna; Devriese, Lisa; Cooreman, Kris; Parmentier, Koen
Abstract: The chemical status of five dredged spoil disposal sites in the Belgian Part of the North Sea is evaluated. A linear mixed-effect model was applied to PCB, PAH and heavy metal data from 2005 to 2014. No decrease in PCB concentrations was found, with even an increase at two disposal sites. Hg/AL ratios increased with 62% at one disposal site (BR&WS2) from 2005 to 2006 to 2013–2014. Cu and Zn concentrations increased at two disposal sites. Additional harbour sampling suggests that the latter is possibly linked to antifouling paints. Based on OSPAR environmental assessment criteria, the current chemical status of the sites suggests no chronic effect of dredged spoil disposal. However, increasing time trend data for PCB, Hg, Cu and Zn demonstrate the importance of monitoring to identify adverse trends. Highlights: PCB concentrations in Belgian marine sediments not decreasing since 2005. Zn and Cu concentrations at dredged spoil disposal sites possibly affected by shipyards. Dredged spoil disposal site monitoring essential to identify adverse time trends.